Evaluating the knowledge about route of drug administration among nursing students using pre and post-test - KALA P; KIRAN B; KUMARASWAMY D; JAMUNA RANI R; CHITRA NS. (International Journal of Pharma and Bio Sciences, 2017)
Present study was aimed to evaluate the knowledge of II year undergraduate Nursing students about routes of drug administration using pre and post-test with multiple choice questions. B.Sc Nursing students attending II year pharmacology classes on the first day were included. Ten multiple choice questions from routes of drug administration were distributed to the students prior to the lecture for answering, followed by didactic power point lecture. At the end of the class, same ten questions were given and answers were collected. Data were analyzed using paired t test in SPSS 19 version. Pre and post-test marks were analyzed using paired t test which showed highly significant p value (0.0001) indicating higher score in the post-test than pre-test. Pre-test and post-test with multiple choice questions is one of the effective methods in the didactic lecture to improve attention and knowledge among students.